PREVALENCE OF DEPRESSION IN FIRST-YEAR MEDICAL STUDENTS AT UNIVERSITAS AIRLANGGA, SURABAYA, INDONESIA - Dina Arini Izzah; Suksmi Yitnamurti; Nancy Margarita Rehatta (Majalah Biomorfologi, 2021)
Background: Depression is a mental disorder with a relatively high prevalence rate in medical students around the world. Medical students are often faced with a variety of pressures ranging from academic to social stress so that the prevalence of depression in medical students tends to be higher than general population. Objective: to find the prevalence of depression in medical students at Universitas Airlangga, Surabaya, Indonesia. Materials and Methods: This research was a descriptive cross-sectional study of first-year medical students at Universitas Airlangga, Surabaya, Indonesia in the academic year of 2017/2018. The data collection was carried out using Beck Depression Inventory II questionnaires as a measurement instrument and was analyzed by SPSS 16.0. Results: From 86 samples obtained from first-year students, 37.20% of them experienced mental conditions that were considered abnormal (mean score of 10.14 ± 7.093), starting from mild mood disturbance (23.26%) to the most severe category, severe depression (1.16%). There was no extreme depression category in this study. Furthermore, mean score of male subjects is 8.57 ± 6.120 while mean score of female subjects is 10.64 ± 7.351. Conclusion: This study revealed that the prevalence of depression in first-year medical students at Universitas Airlangga, Surabaya, Indonesia in the second semester of academic year 2017/2018 was quite high, which was more than one third of the total respondents, while the prevalence in female subjects was higher than in male subjects.